Mediating Effect of Critical Thinking on the Relationship between Personality and Leadership - Sánchez Paredes, Sandro Alberto (Pontificia Universidad Católica del Perú, 2021)
Although personality, leadership, and critical thinking have been widely studied over the years, as well as the relationships between two of those variables, few studies have addressed the relationship between all three variables. This study was aimed at determining the mediating effect of critical thinking on the relationship between personality and leadership by conducting a correlational study to test four hypotheses. The first hypothesis was related to personality and leadership style, the second was related to personality and critical thinking, the third was related to critical thinking and leadership style, and the fourth placed critical thinking as a mediator between personality and leadership style. Partial Least Squares Structural Equation Modeling (PLS-SEM) was applied, using SmartPLS 3 software, on a sample of 139 middle managers from Colombia, Ecuador, and Peru. The subjects completed standardized assessments to determine personality (NEO-PI test), leadership style (MLQ test), and critical thinking (WGCTA test). Only the hypotheses that related personality and transformational leadership, personality and passive-avoidant leadership, and personality and critical thinking, were accepted. The study determined that there is no mediation effect of critical thinking on the relationship between personality and any of the leadership styles, thus calling into question the generalized idea that leaders should be critical thinkers. This study reveals the relevant academic and practical implications, and provides recommendations for practice and future research involving the relationships between personality, leadership, and critical thinking.

Aunque la personalidad, el liderazgo y el pensamiento crítico se han estudiado ampliamente a lo largo de los años, así como las relaciones entre pares de esas variables, pocos estudios han abordado la relación entre las tres variables. Este estudio tuvo como objetivo determinar el efecto mediador del pensamiento crítico sobre la relación entre personalidad y liderazgo mediante la realización de un estudio correlacional para probar cuatro hipótesis. La primera hipótesis se relacionó con la personalidad y el estilo de liderazgo, la segunda se relacionó con la personalidad y el pensamiento crítico, la tercera se relacionó con el pensamiento crítico y el estilo de liderazgo y la cuarta situó el pensamiento crítico como mediador entre la personalidad y el estilo de liderazgo. Se aplicó el Modelo de Ecuación Estructural de Mínimos Cuadrados Parciales (PLS-SEM), utilizando el software SmartPLS 3, en una muestra de 139 mandos intermedios de Colombia, Ecuador y Perú. Los sujetos completaron evaluaciones estandarizadas para determinar personalidad (prueba NEO-PI), estilo de liderazgo (prueba MLQ) y pensamiento crítico (prueba WGCTA). Solo se aceptaron las hipótesis que relacionaron la personalidad y el liderazgo transformacional, la personalidad y el liderazgo pasivo-evitativo, y la personalidad y el pensamiento crítico. El estudio determinó que no existe un efecto mediador del pensamiento crítico en la relación entre la personalidad y ninguno de los estilos de liderazgo, cuestionando así la idea generalizada de que los líderes deben ser pensadores críticos. Este estudio revela las implicaciones académicas y prácticas relevantes, y proporciona recomendaciones para la práctica y la investigación futura que involucran las relaciones entre personalidad, liderazgo y pensamiento crítico.
Keywords: Personalidad; Estilos de liderazgo; Pensamiento crítico; https://purl.org/pe-repo/ocde/ford#5.02.04